The Role of the Family in Development Students in Study Character Building - Sitompul, Liyandasari; Ziah Ulhaq, Rahra (International Journal of Students Education, 2023)
The family has an important and main role in children's development in character education studies both at home and at school. Character education is a form of realizing and developing the character of students who are of good quality in terms of ethics, morals and academic achievement. One of them is the family which is the main forum for a child in forming educational character at home. Involvement of families and children to get to know each other. And the involvement of parents and teachers at school in paying attention to a child's growth and development in class. The problems that arise in forming character education are caused by the lack of parental awareness of character education. Parents prioritize their children's academic achievements and grades over politeness and honesty. This results in an education that is smart but does not have good character, lack of ethics and morals in every child. So overall, parents have the most important role in the development of students in character education studies both at home and in the surrounding social environmentTo prevent bad character in children, parents are expected to be able to provide good parenting and guidance without resorting to violence. Likewise schools, with teachers who teach students how and what are the good character points as a student.